Analysis of Level of Academic Procrastination on Mathematics Assignments - Kristina Warniasih; Savitri Nur Indahsari; Victor Novianto (UM Purwokerto Press, 2024)
This study aims to determine the level of academic procrastination on the mathematics assignment of students at SMP Negeri 11 Yogyakarta. In addition, to find out the causes of students experiencing academic procrastination. The purpose of the study was so that the results of this study can be used as a reference to find solutions to the problems experienced by students. This type of research is descriptive quantitative. The population in this study were students of SMP Negeri 11 Yogyakarta class VIII as many as 136 students. The methods used are questionnaires, interviews, and documentation. The instrument validity technique uses logical validity carried out by material experts and empirical validity with a significant level of 5%. Test the reliability of the instrument using Cronbach's Alpha formula and determine the category of procrastination using SPSS 28.0. Qualitative data analysis uses descriptive qualitative, including data reduction, data presentation, and verification. Test the validity of the data in this study including the credibility test using triangulation techniques. The results showed that there were 21 students in the high category, 69 students in the medium category, and 10 students in the low category. The causes of students experiencing procrastination include a lack of interest in mathematics, difficult math tasks, considering tasks that are less important to do, and lacking the ability to divide time.